Determine the Impact of COVID on Lower-Limb Exoskeleton Robotic System Patents - Pan\(\breve{a}\), Cristina Floriana; R\(\breve{a}\)dulescu, Virginia Maria; P\(\breve{a}\)trascu-Pan\(\breve{a}\), Daniela Maria; B\(\hat{I}\)zdoac\(\breve{a}\), Nicu George (Recent Progress in Science and Technology Vol. 7, 2023)
The evolution of technologies in recent decades has left its mark on implementing robotic systems that help the elderly (and not only) to overcome locomotor difficulties. The concern of researchers in this field has materialized in patent proposals to innovate different types of robotic exoskeleton systems of the lower limbs, some commercially available. In this context, the question arises, "how has the COVID pandemic affected the evolution of the publication of research results in the form of patents. Another question is, "how has the volume of publication or the application of new patents changed in robotic exoskeleton systems?" The present study led to the hypothesis that this pandemic has caused a reduction in the volume of new applications and possibly publications. To validate the study, we compared the data collected in the last decade, distinguishing between periods. In addition, this study used statistical tests to determine the existence of significant changes. The results obtained strengthen the hypothesis we proposed and show that the pandemic had at least an effect on the request for new patents based on the information analyzed from the three databases examined.